Aplikasi Analisis Faktor Konfirmatori untuk Menentukan Reliabilitas Multidimensi - Gaguk Margono (Program Studi Statistika Unisba, 2013)
The aim of this paper is to draw on the application of Confirmatory Factor Analysis (CFA) inStructural Equation Modeling (SEM) to estimate of instrument for measuring attitudes towardstatistics using semantic differential scale. The semantic differential scale is a type of survey questionwhere respondents are asked to rate their opinion on a linear scale between 2 standpoints, theoreticaltypically with 7 levels. It has three dimensions such as evaluation, potency, and activity (EPA). Thisinstrumenthas been tested to 133 studentsof Evaluation Research Program Education (Prodi PEP),Graduate Program in Jakarta State University (PPs UNJ). Reliability refers to accuracy and precisionof a measurement instrument. Multidimensional measurement of internal consistency reliability israrely used in the realm of research. Measurement and computation is described in this article usesan instrument measuring student attitudes toward statistics using semantic differential scale. It canbe concluded that the instrument gauges student attitudes toward statistics using semanticdifferential scale using multidimensional reliability coefficient has a high accuracy when comparedwith a unidimensional reliability coefficient. Expected in advanced research used another formulamultidimensional reliability, included if used SEM.